Free play in sectors to promote autonomy in children of four years - Figueroa Chambergo, Yrma Violeta (2019)
The present research work called: Free play in sectors to promote Autonomy - children of four years - Private Educational Institution “Santa Ana School” - Chiclayo – 2018, is theoretically based on the development process of Autonomy based on Piaget's theory, which considers that children acquire values through their socialization thus developing their autonomy and the theory of Maria Montessori who sustains that the child so that he can learn in a more dynamic and essential way for his age needs the game, stimuli and strategies that lead him to new learnings. The research method used in the present study is pre-experimental, and as a type of research it is applied, the free play workshop in sectors: "I can do it" was used to obtain results and give a precise conclusion to the problem. The population and sample consists of 12 boys and girls of 4 years. A list of Pedagogical Achievement Checks was used as an instrument and workshop of 20 leisure activities based on free play in sectors was applied. Finally, when applying the post-test, the 100% level achieved was obtained; when discussion of results and the expected hypothesis test, it can be concluded that the "I can do it" workshop, based on free play in sectors such as strategies, significantly influenced the development of Autonomy in children of 4 years of the Private Educational Institution "Santa Ana School" of Chiclayo - 2018.